Gas-phase hydrogenation influence on defect behavior in titanium-based hydrogen-storage material; Progress in Natural Science: Materials International; Vol. 27, iss. 1 - Laptev R. S. Roman Sergeevich; Kudiyarov V. N. Victor Nikolaevich; Bordulev Yu. S. Yuri Sergeevich; Mikhaylov A. A. Andrey Anatoljevich; Lider A. M. Andrey Markovich (2017, 2017)
Title screen